x(2-x)(2+x)-(-X-2)=0

Simple and best practice solution for x(2-x)(2+x)-(-X-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2-x)(2+x)-(-X-2)=0 equation:


Simplifying
x(2 + -1x)(2 + x) + -1(-1X + -2) = 0

Multiply (2 + -1x) * (2 + x)
x(2(2 + x) + -1x * (2 + x)) + -1(-1X + -2) = 0
x((2 * 2 + x * 2) + -1x * (2 + x)) + -1(-1X + -2) = 0
x((4 + 2x) + -1x * (2 + x)) + -1(-1X + -2) = 0
x(4 + 2x + (2 * -1x + x * -1x)) + -1(-1X + -2) = 0
x(4 + 2x + (-2x + -1x2)) + -1(-1X + -2) = 0

Combine like terms: 2x + -2x = 0
x(4 + 0 + -1x2) + -1(-1X + -2) = 0
x(4 + -1x2) + -1(-1X + -2) = 0
(4 * x + -1x2 * x) + -1(-1X + -2) = 0
(4x + -1x3) + -1(-1X + -2) = 0

Reorder the terms:
4x + -1x3 + -1(-2 + -1X) = 0
4x + -1x3 + (-2 * -1 + -1X * -1) = 0
4x + -1x3 + (2 + 1X) = 0

Reorder the terms:
2 + 1X + 4x + -1x3 = 0

Solving
2 + 1X + 4x + -1x3 = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 1X + 4x + -2 + -1x3 = 0 + -2

Reorder the terms:
2 + -2 + 1X + 4x + -1x3 = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 1X + 4x + -1x3 = 0 + -2
1X + 4x + -1x3 = 0 + -2

Combine like terms: 0 + -2 = -2
1X + 4x + -1x3 = -2

Add '-4x' to each side of the equation.
1X + 4x + -4x + -1x3 = -2 + -4x

Combine like terms: 4x + -4x = 0
1X + 0 + -1x3 = -2 + -4x
1X + -1x3 = -2 + -4x

Add 'x3' to each side of the equation.
1X + -1x3 + x3 = -2 + -4x + x3

Combine like terms: -1x3 + x3 = 0
1X + 0 = -2 + -4x + x3
1X = -2 + -4x + x3

Divide each side by '1'.
X = -2 + -4x + x3

Simplifying
X = -2 + -4x + x3

See similar equations:

| -6y^2-9x+1=0 | | -3x+6=-2(3x+6) | | -3(5y-7)+2(4y+6)= | | 6(2x-4)=36 | | 5x-(3x-4)=17 | | 4x^2-28x+11=0 | | 6(13-2x)=50-x+46 | | 0+11y=7 | | 0+11y=y | | 2(4x+3)=12x+4-4x+2 | | 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 |

Equations solver categories